1981
DOI: 10.1021/bi00517a005
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 nuclear magnetic resonance study of protonation of methotrexate and aminopterin bound to dihydrofolate reductase

Abstract: Methotrexate, aminopterin, and folate have been synthesized with 90% enrichment of C-2 with 13C. 13C nuclear magnetic resonance has been used to examine the state of protonation of the pteridine ring of these compounds under various conditions and gives much more clear-cut results than most other methods. For the free compounds the following pK values were obtained: methotrexate, 5.73 +/- 0.02 (N-1); aminopterin, 5.70 +/- 0.03 (N-1); folic acid, 2.40 (N-1) and 8.25 +/- 0.05 (N-3, O-4 amide group). The state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
2

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 33 publications
4
62
1
2
Order By: Relevance
“…We observe directly a proton at N1 of MTX, imparting it with a positive charge. This result agrees with nearly all available biochemical and complementary structural data for E. coli and L. casei DHFRs: that the MTX⅐D27 interaction is ionic in nature (45)(46)(47)(48)(49)(50)(51). However, it is in disagreement with the theoretical calculations of Cannon et al (52), who proposed that the MTX N1⅐D27 pair involves a neutral dipole-dipole interaction.…”
Section: Discussionsupporting
confidence: 80%
“…We observe directly a proton at N1 of MTX, imparting it with a positive charge. This result agrees with nearly all available biochemical and complementary structural data for E. coli and L. casei DHFRs: that the MTX⅐D27 interaction is ionic in nature (45)(46)(47)(48)(49)(50)(51). However, it is in disagreement with the theoretical calculations of Cannon et al (52), who proposed that the MTX N1⅐D27 pair involves a neutral dipole-dipole interaction.…”
Section: Discussionsupporting
confidence: 80%
“…There appear to be two major differences between the binding of methotrexate and that of folate: methotrexate is protonated at N1 when bound to the enzyme [2][3][4][5][6][7][8][9][10], while folate is apparently not, and the pteridine ring of methotrexate binds to the enzyme in an orientation which differs by a rotation of about 180 ° about its long axis from that adopted by folate [11][12][13][14]. The recent determination of the crystal structure of the enzyme-trimethoprim complex [15] shows that the orientation of the 2,4-diaminopyrimidine ring in the binding site is very similar to that of the analogous part of methotrexate [11,16].…”
Section: Introductionmentioning
confidence: 99%
“…If the total energy is written as Etot = Ebadh + Eele + EvdW, [5] where Ebadh represents the bond, the angle, and the dihedral AGAB = AGAA' + AGA'B- [7] In state A' the solute has the same bond, angle, dihedral, angle, and dihedral terms. This type of decomposition has been used, in earlier studies (25) on solvation of amino acid side chains, to overcome some sampling difficulties during the conversion of a polar solute to a nonpolar solute in water.…”
Section: Free-energy Perturbation Methodsmentioning
confidence: 99%
“…Several investigators (5,7,27) have suggested that the strong interaction between MTX and DHFR is the result of the ionic reaction between the protonated MTX and the negatively charged Asp-27 in a hydrophobic environment. However, unless the charged group is stabilized by the protein surroundings, the energy gained by the ionic interactions would be lost for desolvating the charged groups.…”
Section: Free-energy Perturbation Methodsmentioning
confidence: 99%
See 1 more Smart Citation